2020
DOI: 10.1097/md.0000000000022684
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of gestational diabetes mellitus and maternal blood glucose levels

Abstract: Previous studies have indicated that the prevalence of gestational diabetes mellitus (GDM) was related to the season. However, there was no relevant information in Asia. The aim of this study was to determine whether there was seasonality of GDM and maternal blood glucose level in Taiwanese women. A total of 6396 pregnancies were enrolled between 2012 and 2014 in this retrospective study. A 2-step approach according to the Carpenter-Coustan criteria was used for GDM diagnosis. A generalized linear m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Women pregnant in winter show the highest prevalence of GDM, and the GDM screening time is approximately 24–28 weeks into pregnancy (6–7.5 months after pregnancy). GDM was mostly diagnosed in the summer, which is consistent with the literature: summer screening yields higher GDM diagnosis rates 30 , 31 . In recent systematic review 32 showed there is mounting evidence that ambient temperature and season during pregnancy is associated with an increased risk of developing GDM and adverse glycemic outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Women pregnant in winter show the highest prevalence of GDM, and the GDM screening time is approximately 24–28 weeks into pregnancy (6–7.5 months after pregnancy). GDM was mostly diagnosed in the summer, which is consistent with the literature: summer screening yields higher GDM diagnosis rates 30 , 31 . In recent systematic review 32 showed there is mounting evidence that ambient temperature and season during pregnancy is associated with an increased risk of developing GDM and adverse glycemic outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the effects of pregnancy season on the GDM and blood glucose level, and the effects of subsequent GDM and elevated blood glucose level on offspring glucose metabolism may also be the potential mechanisms. Previous studies ( 26 , 27 ) have shown the effect of pregnancy season on GDM. Furthermore, seasonal changes in food types, food nutritional value, and seasonal changes in eating habits may increase the risk of type 2 diabetes in adulthood in food-deficit areas or years ( 16 , 28 30 ).…”
Section: Discussionmentioning
confidence: 88%
“…For example, breast cancer incidence has seasonal patterns that seem to vary among global populations 33 . The associated symptoms of diabetes are influenced by seasonality, as reported in the past study that the Gestational Diabetes Mellitus prevalence in Taiwan revealed seasonal variation, with the highest risk occurring in spring and summer due to the post-glucose load level variations 34 , thus may also contribute to the periodicity of the online search volumes. It has also been reported that season has a clinically significant influence over the cognition function in older adults either with or without Alzheimer’s diseases, suggesting the associated symptoms of Alzheimer’s diseases are more likely to be pronounced in the winter and early spring 35 .…”
Section: Discussionmentioning
confidence: 91%